A two-level model for description of steel behavior under thermomechanical loading in the range of martensitic transformations: algorithm for implementation of the model - Isupova, Irina Leonidovna; Тrusov Petr Valentinovich (Computational Continuum Mechanics, 2013)
A model is proposed to describe the behavior of steels under thermomechanical loading with account of martensitic transformations. To construct the model, a multilevel approach based on the use of internal variables in its structure – the parameters characterizing the state and evolution of meso- and microstructure of the material – has been applied. The coupled problem is reduced to the solution of three sub-problems: thermal conductivity, determination of the stress-strain state and estimation of the volume fractions of the coexisting phases. Different types of models have been developed and applied to these sub-problems. The paper presents a detailed algorithm for implementation of the model including all three sub-problems on two scale levels. As an example, a representative volume of the material under simple and complex loading conditions is considered at the macro-level. Numerical experiments have been performed to take into account temperature changes caused by plastic deformation and phase transformations.